Мифы, легенды и сказки удмуртского народа - Кралина Надежда Петровна (Удмуртия, 2019)
Экземпляры: ДО мл.аб. (2020) / Инвентарный номер: 56373 / Цена: 600.00. / Сис.шифр: К82.3(2Рос=Удм) / Авт.знак: М 68 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм).06